PROFIL KONDISI FISIK ATLET KLUB PERSATUAN TENIS MEJA MANDIRI KABUPATEN KAMPAR - Muhammad Ikhsan; Slamet Slamet; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : this research is motivated by the uncontrolled exercise of physicalcondition for the athlete of the mandiri united table tennis club at kampar district. Thisstudy purpose to determine the profile of physical condition for the athlete of themandiri united table tennis club at kampar district. This research is a quantitativedescriptive. The method used is the survey method. The subject of this research is theathlete of the mandiri united table tennis club at kampar district, for 10 people. Theinstruments used were Sit-ups, shoulder and wrist-elevation test, 30 meter run test, Ttestand Multistage fitness test. The data analysis technique used is the castingfrequency in a precentage. The results of this study indicate that the profile of thephysical condition for the athlete of the mandiri united table tennis club at kampardistrict is moderate with the consideration of the highest frequency in the moderatecategory with 6 athletes or 60%. Profile of the physical condition for the athlete of themandiri united table tennis club at kampar district, which is a very good category 1person or 10%, good 1 person or 10%, medium 6 people or 60%, less 2 people or 20%,less than 0 people or 0%.Key words : Physical Condition And Table Tennis